Randomised study of PF-06410293, an adalimumab (ADL) biosimilar, compared with reference ADL for the treatment of active rheumatoid arthritis: results from weeks 26–52, including a treatment switch from reference ADL to PF-06410293. Issue 2 (21st April 2021) - Fleischmann, Roy M; Alvarez, Daniel F; Bock, Amy E; Cronenberger, Carol; Vranic, Ivana; Zhang, Wuyan; Alten, Rieke
Abstract : Objective: To investigate the efficacy, safety, immunogenicity and pharmacokinetics of biosimilar adalimumab (ADL) PF-06410293 (ADL-PF; adalimumab-afzb) versus EU-sourced reference ADL (ADL-EU) in patients with active rheumatoid arthritis (RA) on longer-term treatment and after being switched from ADL-EU to ADL-PF. Methods: In this multinational, double-blind study, patients with active RA were initially randomised to ADL-PF or ADL-EU for 26 weeks (treatment period (TP) 1). At the start of TP2 (weeks 26–52), patients in the ADL-EU arm were blindly re-randomised 1:1 to remain on ADL-EU (ADL-EU/ADL-EU; n=135) or switched to ADL-PF (ADL-EU/ADL-PF; n=134); patients receiving ADL-PF continued blinded treatment (ADL-PF/ADL-PF; n=283). Results: The American College of Rheumatology 20% improvement (ACR20) response rates were comparable between treatment groups at all visits during TP2. At week 52, ACR20 response rates were 82.7% (ADL-PF/ADL-PF), 79.3% (ADL-EU/ADL-EU) and 84.3% (ADL-EU/ADL-PF). Other measures of deep response (ACR50/70, ACR/EULAR-defined remission, EULAR good response, and Disease Activity Score in 28 Joints Based on High-Sensitivity C-Reactive Protein <2.6) and Health Assessment Questionnaire−Disability Index were maintained over TP2 and comparable between groups. Treatment-emergent adverse events were reported in 43.5% (ADL-PF/ADL-PF), 44.4% (ADL-EU/ADL-EU) and 38.3% (ADL-EU/ADL-PF) of patients; there were no clinically meaningful differences in the safety profiles between groups. The percentage of patients who were antidrug antibody positive was comparable overall among ADL-PF/ADL-PF (47.3%), ADL-EU/ADL-EU (54.1%) and ADL-EU/ADL-PF (45.9%). Conclusions: The similar efficacy, safety, immunogenicity and pharmacokinetics of ADL-PF and ADL-EU, maintained up to week 52, were unaffected by blinded treatment switch from ADL-EU to ADL-PF at week 26. Trial registration number: ClinicalTrials.gov identifier: NCT02480153 ; EudraCT number: 2014-000352-29.